PATHOPHYSIOLOGY OF THE KIDNEYS AND KIDNEY DISEASES - Yusupova Maftuna Azamatovna, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: The kidneys are vital organs responsible for maintaining homeostasis in  the  human  body.  They  play  a  crucial  role  in  blood  filtration,  waste  excretion, electrolyte  and  fluid  balance,  acid-base  regulation,  and  blood  pressure  control. Pathophysiological  processes  affecting  the  kidneys  can  lead  to  various  diseases, including  acute  and  chronic  kidney  failure,  nephritis,  nephrotic  syndrome,  kidney stones, and other disorders.